Progrès technique augmentant le produit marginal des facteurs et productivité dans l’industrie manufacturière canadienne - May, J.; Denny, M. (L'Actualité économique, 1978)
The purpose of this paper is to establish a relation between the empirical estimates of productivity and technical change. Few studies have tended to give estimates of that relation. The measuring of productivity involves the use of an implicit production function. Moreover, measures of productivity are estimates of the rates of change of Hicks-neutral technical change.The paper suggests that non-sophisticated measures of technical change may be replaced since they offer inadequate description of temporal change in technology. Finally, it would be useful to continue to develop econometrics models of technical change.